Peers, Gender, and Long-Term Depression - Corrado Giulietti; Michael Vlassopoulos; Yves Zenou (Research Institute of Industrial Economics (IFN), 2020)
This study investigates whether exposure to peer depression in adolescence affects own depression in adulthood. We find a significant long-term depression peer effect for females but not for males in a sample of U.S. adolescents who are followed into adulthood. An increase of one standard deviation of the share of own-gender peers (schoolmates) who are depressed increases the probability of depression in adulthood by 2.6 percentage points for females (or 11.5% of mean depression). We also find that the peer effect is already present in the short term when girls are still in school and provide suggestive evidence for why it persists over time. In particular, we show that peer depression negatively affects the probability of college attendance and the likelihood of working, and leads to a reduction in income of adult females. Further analysis reveals that individuals from families with a lower socioeconomic background are more susceptible to peer influence, thereby suggesting that family can function as a buffer.
Keywords: I12; Z13; 330; Peer effects; Depression; Contagion; Gender; Family background; Adolescence; Policy